O (em)baralhamento como estratégia discursiva da campanha como estratégia discursiva da campanha de vacinação da covid-19 do Ministério da Saúde no Brasil - Wecki, Matheus Rocha (2022)
This research has as its object of study the campaigns developed by the Ministry of Health (MS) to combat the Covid-19 pandemic, and proposes to analyze the discursive strategies of the campaigns carried out by Zé Gotinha, discuss the specificities of invisibility strategies , visibility and modulation of desired focuses and highlight the strategies of invisibility, reduction and targeting of visibility adopted by the Brazilian Ministry of Health during the SARS-CoV-2 pandemic, in the aforementioned campaigns. We chose to carry out an exploratory research (MALHOTRA, 2012; GIL, 2010) developed through bibliographic and documentary surveys and a case study (GIL, 2010; YIN, 2015). Regarding the theoretical-methodological approach, we used discourse analysis (AD), proposed by Charaudeau (2004; 2012; 2019) and invisibility strategies (SILVA, 2018) to support our analysis of the Ministry's campaigns against Covid-19. of health. Harari (2020), Antunes (2020), Morin (2020) are some of the authors who help us to reflect on the pandemic society, while Han (2017), Wolton (2011), Castells (2004) support the discussions about the hyperconnected society . The vaccination campaign against Covid-19, which made the character Zé Gotinha a symbol of the National Immunization Program (PNI) in Brazil, reveals the predominance of shuffling and shuffling strategies that seek to make facts and perspectives visible and invisible (SILVA, 2018). With clear strategies to influence society to take care of its family, its income and Brazil, the Federal Government, through the Ministry of Health and the characters of the Gotinha family, evidences, in three discursive views, of prescription, description and information (CHARADEAU, 2019), their intentions.